SEEG-guided radiofrequency thermocoagulation of epileptic foci in the paediatric population: Feasibility, safety and efficacy. (August 2019) - Chipaux, Mathilde; Taussig, Delphine; Dorfmuller, Georg; Dorison, Nathalie; Tisdall, Martin M.; Boyd, Stewart G.; Thornton, Rachel; Eltze, Christin; Fohlen, Martine; Cross, Helen J.; Ferrand-Sorbets, Sarah
Highlights: RFTC is a safe method for the paediatric population. RFTC combines diagnostic and therapeutic intervention. RFTC can result in seizure control for several months with improved life quality. Improvement in seizure frequency is seen in 2/3 of our paediatric patients. Palliative technique when the epileptogenic zone overlaps with eloquent areas. Abstract: Purpose: Focal epilepsy in children may be refractory to pharmacological treatment and surgical resection may be an appropriate option. When invasive electroencephalogram is required in the presurgical evaluation, depth electrodes can be used to create focal lesions in the epileptogenic zone using radiofrequency thermocoagulation (RFTC), to disrupt the epileptogenic zone. Methods: This study aimed to assess the efficacy and safety of RFTC in a paediatric population of 46 patients. Results: The mean age of onset was 3.3 years and the mean age at SEEG was 8.2 years. MRI lesions were identified in 71.7% of the series, among them 60% of malformation of cortical development. 43.5% of the patients were seizure free at 1 month, 26.1% were responders. The mean duration of improvement was 6.8 months. 8 children were seizure free for >8 months and among them, 6 are currently seizure free for 8–24 months. 5 patients had functional deficits post-procedures, transient in 4 patients and prolonged in one of whom. 3/5 were anticipated following the results of cortical stimulation. Multivariate analysis found 3 independent criteria linked to RFTC efficiency one month after RFTC: frequency of the seizures before RFTC, age and number of contacts used. Conclusion: RFTC is a safe method for the paediatric population providing important predictive information for surgical resection. An improvement in seizure frequency, often transient, is seen in 2/3 of our patients. RTFC could be useful as a palliative technique for children with an epileptogenic zone overlapping with eloquent areas, with minimal risk of sequelae.